Lipid and endothelium-related genes, ambient particulate matter, and heart rate variability—the VA Normative Aging Study. Issue 1 (13th July 2009) - Ren, C; Baccarelli, A; Wilker, E; Suh, H; Sparrow, D; Vokonas, P; Wright, R; Schwartz, J
Abstract : Background: Many studies have shown that exposures to air pollution are associated with cardiovascular events, although the mechanism remains to be clarified. To identify whether exposures to ambient particles act on autonomic function via the lipid/endothelial metabolism pathway, whether effects of particulate matter <2.5 μm in aerodynamic diameter (PM2.5 ) on heart rate variability (HRV) were modified by gene polymorphisms related to those pathways were evaluated. Methods: HRV and gene data from the Normative Aging Study and PM2.5 from a monitor located a kilometre from the examination site were used. A mixed model was fitted to investigate the associations between PM2.5 and repeated measurements of HRV by gene polymorphisms of apolipoprotein E (APOE), lipoprotein lipase (LPL) and vascular endothelial growth factor (VEGF) adjusting for potential confounders chosen a priori. Results: A 10 μg/m 3 increase in PM2.5 in the 2 days before the examination was associated with 3.8% (95% CI 0.2% to 7.4%), 7.8% (95 CI 0.4% to 15.3%) and 10.6% (95% CI 1.8% to 19.4%) decreases of the standard deviation of normal-to-normal intervals, the low frequency and the high frequency, respectively. Overall, carriers of wild-type APOE, LPL and VEGF genes had stronger effects of particles on HRV than those with hetero- or homozygous types. Variations of LPL-N291S, LPL-D9N and APOE-G113C significantly modified effects of PM2.5 on HRV. Conclusion: Associations between PM2.5 and HRV were modified by gene polymorphisms of APOE, LPL and VEGF; the biological metabolism remains to be identified.